CCR7-mediated T follicular helper cell differentiation is associated with the pathogenesis and immune microenvironment of spinal cord injury-induced immune deficiency syndrome - Li, Chaochen; Wu, Chunshuai; Xu, Guanhua; Liu, Yang; Chen, Jiajia; Zhang, Jinlong; Hong, Hongxiang; Ji, Chunyan; Cui, Zhiming (Frontiers in Neuroscience, 2022)
Spinal cord injury-induced immune deficiency syndrome (SCI-IDS) is a disorder characterized by systemic immunosuppression secondary to SCI that dramatically increases the likelihood of infection and is difficult to treat. T follicular helper (Tfh) cells regulated by chemokine receptor CCR7 are associated with SCI-IDS after acute SCI. The present study explored the roles of CCR7 in SCI-IDS occurrence and immune microenvironment composition. Gene expression profile data of peripheral blood leukocytes from SCI and non-SCI subjects were collected from the Gene Expression Omnibus database. According to differential gene expression analysis, a protein-protein interaction (PPI) network, and risk model construction, the CCR7 expression level was prominently related to acute SCI and CCR7 expression was significantly downregulated after acute SCI. Next, we constructed a clinical prediction model and used it to identify patients with acute SCI. Using Gene Ontology (GO) analysis and gene set enrichment analysis (GSEA), we discovered that immune-related biological processes, such as T cell receptor signaling pathway, were suppressed, whereas chemokine-related signaling pathways were activated after acute SCI. Immune infiltration analysis performed using single sample GSEA and CIBERSORT suggested that Tfh cell function was significantly correlated with the CCR7 expression levels and was considerably reduced after acute SCI. Acute SCI was divided into two subtypes, and we integrated multiple classifiers to analyze and elucidate the immunomodulatory relationships in both subtypes jointly. The results suggested that CCR7 suppresses the immunodeficiency phenotype by activating the chemokine signaling pathway in Tfh cells. In conclusion, CCR7 exhibits potential as a diagnostic marker for acute SCI.